2020
DOI: 10.4018/ijea.2020070102
|View full text |Cite
|
Sign up to set email alerts
|

Consumer E-Loyalty for E-Grocery Shopping in a Metro City of India

Abstract: This study focuses on the e-loyalty of the grocery consumers. Understanding online behavior in developing countries is an emerging issue in these days. The purpose of this research is to examine the effects of antecedents of flow on attitude and perceived ease of use in the context of online grocery purchase behavior in a developing country perspective. Further, the study also examines the role of attitude and perceived ease of use in building e-loyalty. The present study analyzes the data of 250 respondents c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
3
1
Order By: Relevance
“…Thus, hypothesis 6 (H6) is not supported. This finding is different from previous studies (Bahari et al, 2018;Khan & Khan, 2020;Wilson et al, 2021), which state that perceived ease of use has a significant effect on loyalty. However, a study found that perceived ease of use has no impact on loyalty to social media users based on Online Brand Community (Potgieter & Naidoo, 2017) The perceived ease of use in conducting transactions using e-commerce, apparently does not necessarily make millennials loyal.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, hypothesis 6 (H6) is not supported. This finding is different from previous studies (Bahari et al, 2018;Khan & Khan, 2020;Wilson et al, 2021), which state that perceived ease of use has a significant effect on loyalty. However, a study found that perceived ease of use has no impact on loyalty to social media users based on Online Brand Community (Potgieter & Naidoo, 2017) The perceived ease of use in conducting transactions using e-commerce, apparently does not necessarily make millennials loyal.…”
Section: Discussioncontrasting
confidence: 99%
“…Bem's [61] self-perception theory suggests that people strive to rationalize their actions and mitigate cognitive dissonance by aligning inconsistent opinions, views, or conduct. When in a state of intellectual absorption, individuals derive pleasure and SAT from engaging in technological activities, leading to a reduction in conflicts during this pleasant and enjoyable state [62][63][64][65]. Building on these concepts, it is hypothesized that profoundly motivated students would perceive online learning platforms as beneficial.…”
Section: Flow and Perceived Usefulnessmentioning
confidence: 99%
“…This study focuses on determining the factors that influence consumer adoption of OGS. Online grocery shopping falls in the service innovation category (Khan & Khan 2020;López-Nicolás et al 2008). Consumers are accustomed to shopping groceries from traditional brickand-mortar grocery stores, in which they have to visit the store and select grocery merchandise.…”
Section: Theoretical Framework For Consumer Technology Adoptionmentioning
confidence: 99%